Choroidal circulation disturbance is an initial factor in outer retinal degeneration in rats under simulated weightlessness - Mu, Yuxue; Wei, Dongyu; Yao, Lilingxuan; Xu, Xinyue; Li, Shaoheng; Cao, Ruidan; Chen, Tao; Zhang, Zuoming (Frontiers in Physiology, 2023)
Objective: Microgravity contributes to ocular injury yet the underlying mechanism remains unclear. This study aims to elucidate the mechanism behind choroidal circulation disorder and outer retinal degeneration in rats with simulated weightlessness.Methods: Optical coherence tomography angiography (OCTA) was used to evaluate choroidal circulation and retinal morphological alterations in rats with weightlessness simulation. Electroretinogram and transmission electron microscopy were used to examine the ultrastructure and function of the choroid and outer retina. Furthermore, histological and terminal deoxynucleotidyl transferase deoxyuridine dUTP nick-end labeling (TUNEL) staining was used to monitor retinal morphology.Western blotting was performed to analyze the expressions of blood-retinal outer barrier function-related proteins (Cx43, ZO-1, and occludin).The choroidal thickening was observed from the fourth week of simulated weightlessness (P < 0.05), and choroidal capillary density started to decline by the fifth week (P < 0.05). Transmission electron microscopy revealed that the choroidal vessels were open and operating well by the fourth week. However, most of the mitochondria within the vascular endothelium underwent mild swelling, and by the fifth week, the choroidal vessels had various degrees of erythrocyte aggregation, mitochondrial swelling, and apoptosis. Additionally, ERG demonstrated a decline in retinal function beginning in the fifth week (P < 0.05). TUNEL staining revealed a significantly higher apoptotic index in the outer nuclear layer of the retina (P < 0.05). At the sixth week weeks of simulated weightlessness, OCTA and hematoxylin and eosin (HE) staining of retinal sections revealed that the outer nuclear layer of the retina started to become thin (P < 0.05). Results from western blotting revealed that Cx43, ZO-1, and occludin exhibited decreased expression (P < 0.05).Conclusions: Based on our findings in a rat model of simulated weightlessness, choroidal circulation disturbance induced by choroidal congestion is the initial cause of outer retinal degeneration. Blood-retinal barrier disruption is significant in this process.